2006
DOI: 10.1038/sj.bjc.6602973
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and cost-effectiveness of interferon-alpha in malignant melanoma: results from randomised trial

Abstract: A definitive conclusion regarding the value of low-dose extended duration adjuvant interferon-alpha therapy in the treatment of malignant melanoma is only possible once data on health-related quality of life (HRQoL) and costs have been considered. This trial randomised 674 patients to interferon alpha-2a (3 megaunits three times per week for 2 years or until recurrence) or placebo. Health-related quality of life (QoL) was to be assessed up to 60 months using the European Organisation for Research and Treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 25 publications
2
27
1
3
Order By: Relevance
“…The literature search identified 19 articles and 1 abstract (published between 2003 and 2011), in which were described 7 cost-of-illness analyses [9,10,11,12,13,14,15], 1 cost-effectiveness analysis [16] and 13 cost-utility analyses [16,17,18,19,20,21,22,23,24,25,26,27,28]. …”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified 19 articles and 1 abstract (published between 2003 and 2011), in which were described 7 cost-of-illness analyses [9,10,11,12,13,14,15], 1 cost-effectiveness analysis [16] and 13 cost-utility analyses [16,17,18,19,20,21,22,23,24,25,26,27,28]. …”
Section: Resultsmentioning
confidence: 99%
“…Specifically, decreases in quality-of-life during IFN-a treatment for advanced melanoma were offset by reduced risk of recurrence and mortality when vignette-based utilities were applied (Kilbridge et al, 2002;Crott, 2004;Crott et al, 2004). In contrast, IFN was only marginally better in treating melanoma than was BSC when generic EQ-5D utilities were used (Dixon et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Health status utility assessments enable the quantification of preferences for health outcomes and the estimation of qualityadjusted life expectancy. Utility measurement in melanoma to date has primarily focused on toxicities associated with interferon (IFN) therapy (Kilbridge et al, 2001;Dixon et al 2006). No studies have obtained utilities for a broader set of health states that capture both the intended (clinical response) and unintended (toxicity) effects of available treatments for advanced melanoma.…”
mentioning
confidence: 99%
“…Patients experience a deterioration of QL around the time of primary diagnosis, disease progression, and during systemic therapy [504,513,518,652,660,668,674,675]. Predisposing factors regarding QL progression have been insufficiently validated, albeit some studies have indicated a negative correlation with female gender, preexisting depression, lower social status, and lack of coping [655,676].…”
Section: Quality Of Lifementioning
confidence: 99%